Comparative effectiveness of follow-up imaging approaches in pancreatic cancer. (September 2014) - Reeder-Hayes, Katherine E; Freburger, Janet; Feaganes, John; Peacock Hinton, Sharon; Henderson, Louise M; Massing, Mark; Schenck, Anna P; Stearns, Sally C; Carpenter, William R; Chen, C; Khandani, Amir H
Aim: Although PET imaging is sometimes used in follow-up of pancreatic cancer, evidence regarding comparative effectiveness of PET and older imaging modalities is limited.Patients & methods: Linked cancer registry and Medicare claims data were analyzed to examine patterns of imaging and effects on treatment patterns and survival among newly diagnosed pancreatic cancer patients from 2003 to 2007.Results: 12% of patients received PET during follow-up. In a time-varying exposure model, computed tomography/MRI was associated with lower mortality risk relative to PET in surgical patients (HR: 0.66; 95% CI: 0.52–0.83). In a subset analysis, type of follow-up imaging before 180 days was not associated with mortality after 180 days (computed tomography/MRI vs PET; hazard ratio: 0.98; 95% CI: 0.84–1.16).Conclusion: Follow-up PET is uncommon among Medicare beneficiaries with pancreatic cancer, and is generally used late in the disease course. This pattern of PET use was not associated with decreased mortality risk compared with conventional imaging.